Answer:
5
Explanation:
First you would multiply -5 by everything in parenthesis so...
25 - 3x= -5 + 5x - 2x
Then 5x- 2x..
25 - 3x= -5 + 3x
Add -3x to both sides
25 = -5 + 6x
Add 5 to both side
30= 6x
Divide 6 on both side
5 = x
Hope this helped :)
25 - 3x = -5(1 - x) - 2x
We have to first get rid of the parenthesis:
==> -5
==> 5x
So now you should have:
25 - 3x = -5 + 5x - 2x
Combine like terms:
25 - 3x = -5 + 3x
Add 3x to both sides:
+ 3x = + 3x
And you should have:
Add 5 to both sides:
+5 = +5
30 = 6x
Divide 6 to both sides:
=
6.5m questions
8.6m answers